Patient‐reported outcomes enhance the survival prediction of traditional disease risk classifications: An international study in patients with myelodysplastic syndromes. Issue 6 (12th December 2017) - Efficace, Fabio; Cottone, Francesco; Abel, Gregory; Niscola, Pasquale; Gaidano, Gianluca; Bonnetain, Franck; Anota, Amelie; Caocci, Giovanni; Cronin, Angel; Fianchi, Luana; Breccia, Massimo; Stauder, Reinhard; et al.
Abstract : BACKGROUND: Current prognostic systems for myelodysplastic syndromes (MDS) are based on clinical, pathologic, and laboratory indicators. The objective of the current study was to develop a new patient‐centered prognostic index for patients with advanced MDS by including self‐reported fatigue severity into a well‐established clinical risk classification: the International Prognostic Scoring System (IPSS). METHODS: A total of 469 patients with advanced (ie, IPSS intermediate‐2 or high‐risk) MDS were analyzed. Untreated patients (280 patients) were recruited into an international prospective cohort observational study to create the index. The index then was applied to an independent cohort including pretreated patients with MDS from the Dana‐Farber Cancer Institute in Boston, Massachusetts (189 patients). At baseline, patients completed the European Organization for Research and Treatment of Cancer Quality of Life Questionnaire‐Core 30 (EORTC QLQ‐C30). RESULTS: A new prognostic index was developed: the FA‐IPSS(h), in which FA stands for fatigue and h for higher‐risk. This new risk classification enabled the authors to distinguish 3 subgroups of patients with distinct survival outcomes (ie, risk‐1, risk‐2, and risk‐3). Patients classified as FA‐IPSS(h) risk‐1 had a median overall survival (OS) of 23 months (95% confidence interval [95% CI], 19‐29 months), whereas those with risk‐2 had a median OS of 16 months (95% CI, 12‐17 months) and those with risk‐3 had a median OS of 10 months (95% CI, 4‐13 months). The predictive accuracy of this new index was higher than that of the IPSS alone in both the development cohort as well as in the independent cohort including pretreated patients. CONCLUSIONS: The FA‐IPSS(h) is a novel patient‐centered prognostic index that includes patients' self‐reported fatigue severity. The authors believe its use might enhance physicians' ability to predict survival more accurately in patients with advanced MDS. Cancer 2018;124:1251‐9. © 2017 American Cancer Society . Abstract : Patient‐reported outcomes may improve the accuracy of the survival prediction of traditional risk classifications for patients with myelodysplastic syndromes. A new prognostic score for patients with higher‐risk myelodysplastic syndromes, based on both disease‐related factors and patient‐reported outcomes, has been developed and may facilitate more tailored treatment decisions for these patients.